(untitled) (Physical Education, Health and Social Sciences, 2025)
This study analyzes Bilawal Bhutto’s speech as a reflection of the Pakistani community’s perception and the country’s stance on pressing global issues. The speech addresses key concerns such as climate catastrophe, terrorism, regional conflicts, COVID-19, and Islamophobia, positioning Bhutto as a global leader during crises. The study has used Fairclough’s three-dimensional model for the analysis of the data through a mixed-method research approach, where frequencies of key terms have been retrieved quantitatively, while the interpretation of the speech has been carried out through the lens of the second layer of the 3D model. Discursive strategies like intensification, referential nomination, and prediction are employed to engage the audience and reinforce his persuasive appeal. His speech highlights the urgency of global cooperation in confronting shared challenges.